Evaluation of Growth Performance and Effect of Quality of Eggs of Japanese Quails at Different Levels of Zinc Supplementation under Agro-climatic Condition of Mizoram, India - Lalliankimi, H.; Patra , Gautam; Hmar, Lalnuntluangi; Zosangpuii; Fanai, Rody L. (International Journal of Poultry Science, 2017)
Background and Objective: Zinc (An essential trace element) has an important function in metabolic activities such as protein synthesis, carbohydrate metabolism, reproduction, growth and a variety of biochemical reactions. The zinc ion is a co-factor of many enzymes and a component of metalloenzymes that participates in a number of metabolic processes. In quails, the deficiency of zinc is characterized by slow growth, abnormal feathering, labored respiration, in-coordinated gait, loss of appetite, decrease in egg production and reproductive performance, problems in bone and skin development and also increased mortality. The aim of this study was to determine the growth performance and egg quality of Japanese quails under different levels of zinc supplementation. Methodology: In order to carry out the experiment, a total of 400 days-old quail chicks were randomly selected and sub-divided into four groups i.e., C, T1, T2 and T3 having hundred quails with 10 replicates having 10 quail chicks in each which were supplemented with zinc oxide powder at the rate of 0, 25, 50 and 75 mg kg–1 of diet respectively. The quails were reared under deep litter system using paddy husk as litter material. The birds were fed twice daily at 6:00 am in the morning and 4:30 pm in the afternoon with basal diet of broiler pre-starter and starter rations containing 22 and 18 mg of zinc, respectively. Small portions of the basal diet were first mixed with the respective amount of zinc oxide powder; this small amount was then mixed with a larger quantity of the basal diet until the total quantity was homogenous. Results: The inclusion of zinc in the diet had no significant effect on growth performance in terms of day old body weight, 5th week body weight and daily gain. Zinc supplementation was found to have significant effect in T1, T2 and T3 on albumen index but no significant effects were observed among treatment groups with respect to egg weight, shape index, yolk index, yolk %, albumen %, shell weight % and Haugh unit. Conclusion: The results showed that zinc supplementation at the rate of 50 mg kg–1 of feed and 75 mg kg–1 of feed have significant effect on the albumen index but not on other quality parameters or on body weight gain in terms of day old body weight, 5th week body weight as daily gain.